The Role of Ethics in Decision Making by the Constitutional Court on the Age Limit for Presidential and Vice Presidential Candidates - Khair, Otti Ilham; Syafri, Wirman (Universitas Muhammadiyah Ponorogo, 2024)
This research aims to analyze the role of ethics in the decision of the Constitutional Court (MK) regarding the age limit of presidential and vice presidential candidates and its impact on public views and moral principles in the political system of law and government in Indonesia. The issuance of Constitutional Court Decision Number 90/PUU-XXI/2023 in Indonesia has caused controversy. Through the framework of ethical theories, such as deontology, utilitarianism, leadership ethics, and political ethics and governance ethics, this study reveals how the Constitutional Court's decision raises ethical questions about the Court's moral obligations, the impact on public welfare, individual rights, and moral values in politics. The research method is based on a qualitative method with the type of research used is a literature study. The results show that there are ethical violations in the Constitutional Court's decision-making that have an impact on the moral aspects of the political, legal and governmental system in Indonesia. The Constitutional Court needs to uphold ethics, so that the honor and dignity of law enforcers are well maintained.